(+)-Abscisic Acid 8′-Hydroxylase Is a Cytochrome P450 Monooxygenase - Krochko, Joan E. (American Society of Plant Physiologists, 1998)
Abscisic acid (ABA) 8′-hydroxylase catalyzes the first step in the oxidative degradation of (+)-ABA. The development of a robust in vitro assay has now permitted detailed examination and characterization of this enzyme. Although several factors (buffer, cofactor, and source tissue) were critical in developing the assay, the most important of these was the identification of a tissue displaying high amounts of in vivo enzyme activity (A.J. Cutler, T.M. Squires, M.K. Loewen, J.J. Balsevich [1997] J Exp Bot 48: 1787–1795). (+)-ABA 8′-hydroxylase is an integral membrane protein that is localized to the microsomal fraction in suspension-cultured maize (Zea mays) cells. (+)-ABA metabolism requires both NADPH and molecular oxygen. NADH was not an effective cofactor, although there was substantial stimulation of activity (synergism) when it was included at rate-limiting NADPH concentrations. The metabolism of (+)-ABA was progressively inhibited at O(2) concentrations less than 10% (v/v) and was very low (less than 5% of control) under N(2). (+)-ABA 8′-hydroxylase activity was inhibited by tetcyclacis (50% inhibition at 10(−6) m), cytochrome c (oxidized form), and CO. The CO inhibition was reversible by light from several regions of the visible spectrum, but most efficiently by blue and amber light. These data strongly support the contention that (+)-ABA 8′-hydroxylase is a cytochrome P450 monooxygenase.